“Your wall cannot divide us”: Graffiti in Cyprus and insights into conflict-affected landscapes - Haworth, Billy Tusker; Lepp, Eric; Arthur, Catherine; Vogel, Birte (Street Art & Urban Creativity, 2022)
Graffiti in conflict-affected settings offers alternative understandings of local experiences and international challenges that intertwine with everyday routines and spaces. Urban walls deliver canvases to write, tag, and paint to express grievances and aspirations for more peaceful futures, illuminate societal concerns, and offer solidarity on issues that sit within and outside the confines of historical and present-day division. In this expanded visual essay, we explore the publicly available resource of graffiti to gain insights into the challenges and priorities of Cyprus’ conflict-affected landscape. Drawing on observations on both Greek-Cypriot and Turkish-Cypriot sides of the United Nations Buffer Zone, we explore the ways in which graffiti provides space to recognise alternative voices in a society where official and media discourses remain characterised by language of difference and political division. Insights gained through walking surveys conducted in June 2019 were augmented by discussions with local experts to further contextualise the observed graffiti content. We demonstrate the potential value for academics, policymakers, and practitioners of analysing the languages, symbols, and messages of graffiti. We conclude that this initial exploration establishes graffiti as more than ‘vandalism’ and expands our knowledge of conflict-affected landscapes as an indicator of the everyday and the interactions, priorities, and spatial politics of local people.